Influence of services quality on customer satisfaction towards Hotel Sentral Riverview Melaka / Nur Dini Zafirah Suhaimi - Suhaimi, Nur Dini Zafirah (Faculty of Business and Management, 2019)
The main objectives of this study were to identify the factors that influence customer satisfaction towards Hotel Sentral Riverview Melaka.. The variables included in this research are tangible, reliability, responsiveness, assurance and empathy as independent variables and customer satisfaction as the dependent variable. A survey questionnaire which consisted of seven sections, Section A consists of the respondents ' demographic data Next, Section B until Section F was related to the independent variables while in Section G is related to dependents variables. 125 respondents from guests who stay on the Hotel Sentral Riverview Melaka were selected as a sample. Cronbach’s Alpha was used to determine the reliability and validity of the questionnaire. From the findings, there were a strong relationship between tangible, reliability, assurance and empathy with customer satisfaction. However, there were weak relationship between responsiveness and customer satisfaction with correlation value 0.224. Future researchers could concentrate on determining assurance that influence customer satisfaction when responsiveness is not a factor and reasons for place is currently becoming the leading factor in determining customer satisfaction.